Generalized vs. specific locus of control expectancies of chief executive officers - Boone, Christophe; Brabander, Bert De (Strategic Management Journal, 1993)
Abstract Hodgkinson (1992) recently advocated in this journal that measures of generalized control expectancies, such as the well known Rotter I‐E scale (Rotter, 1966), are not suited to study the relationship between the locus of control beliefs of Chief Executive Officers (CEOs) on the one hand and strategic, structural and performance variables on the other hand. According to Hodgkinson (1992) a more specific scale, measuring strategic control expectancies, should be used in future research. We argue and empirically illustrate that such a methodology will not lead to interesting research results in the ‘strategic leadership’ domain. More specifically, measures of firm‐specific control expectancies are likely to be influenced by the CEO's perception of the situational context of the firm and are therefore not indicative of fundamental personality differences between CEOs. Consequently, such measures cannot give an answer to the basic research question whether and why the personality of CEOs plays an important role in explaining organizational behavior and performance.